2010
DOI: 10.1111/j.1601-5223.2010.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution pattern of rDNA ITS in Avena and phylogenetic relationship of the Avena species (Poaceae: Aveneae)

Abstract: Ribosomal ITS sequences are commonly used for phylogenetic reconstruction because they are included in rDNA repeats, and these repeats often undergo rapid concerted evolution within and between arrays. Therefore, the rDNA ITS copies appear to be virtually identical and can sometimes be treated as a single gene. In this paper we examined ITS polymorphism within and among 13 diploid (A and C genomes), seven tetraploid (AB, AC and CC genomes) and four hexaploid (ACD genome) to infer the extent and direction of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 96 publications
(207 reference statements)
2
17
0
Order By: Relevance
“…It is noteworthy that the AABB genome tetraploid species A. agadiriana was separated from the other AABB genome tetraploid species and clustered together with A c A c genome diploid species A. canariensis, and showed a close relationship with the polyploid species with the A and C genome. This result was supported by morphological (Loskutov & Rines 2011;Ladizinsky 2012) and genomic evidence (Peng et al 2008;Peng et al 2010aPeng et al , 2010bPeng et al , 2010c. Therefore, the genomic assignment of this species should be reconsidered, as Loskutov suggested (2008).…”
Section: Relationships Among Avena Speciessupporting
confidence: 42%
“…It is noteworthy that the AABB genome tetraploid species A. agadiriana was separated from the other AABB genome tetraploid species and clustered together with A c A c genome diploid species A. canariensis, and showed a close relationship with the polyploid species with the A and C genome. This result was supported by morphological (Loskutov & Rines 2011;Ladizinsky 2012) and genomic evidence (Peng et al 2008;Peng et al 2010aPeng et al , 2010bPeng et al , 2010c. Therefore, the genomic assignment of this species should be reconsidered, as Loskutov suggested (2008).…”
Section: Relationships Among Avena Speciessupporting
confidence: 42%
“…The sub-ordinate groups 1 and 2 were resulted from the first major group A, while the sub-ordinate group 3 was resulted from the second major group B, but the sub-ordinate groups 4 and 5 were resulted from the third major group C (Fig. 1) has remained largely problematic, some taxonomic treatments related to the avenoids have focused on particular genera, like Trisetum (Edgar, 1998;Randall and Hilu, 1986), Helictotrichon (Grebenstein et al, 1998), Avena (El-Rabey, 2008;Peng et al, 2010;Rodionov et al, 2005), Deschampsia (Chiapella, 2007), Anthoxanthum (Pereira et al, 2007), Alopecurus (Dogan, 1999), Phleum (Scholz, 1999), and Calamagrostis (Hai-Ying et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, A. barbata appeared closer to them due to the characters similarity, except the presence of macrohairs, while, A. sativa differ from the other three species by the presence of macrohairs and elliptic acuminate glumes, so it appeared as monophyletic species. The placement of all Avena representatives in one group matches with the classification systems constructed by Loskutov (2007), by studying the relationships of genomes of different Avena species at each ploidy level, and (Peng et al, 2010) through studying the evolution pattern of rDNA ITS in Avena and phylogenetic relationship of the Avena species.…”
Section: Observations Of Charactersmentioning
confidence: 99%
“…The results in the present study showed that there are more variations in ITS1 and ITS2 between the related animals. Among the available nuclear sequences, ITS sequences have been used successfully in studying phylogenetic and genomic relationships of plants at lower taxonomic levels (Nieto et al, 2004;Liu et al, 2006;Peng et al, 2010), and the evolution of the rRNA genes in organisms is highly conservative. The variations in the rRNA genes occur slowly and are more conservative than in the whole genome of the organism.…”
Section: Analysis Of Homology and Evolution Of The Rrna Gene Family Omentioning
confidence: 99%